Recognition and Disclosure Reliability: Evidence from SFAS No. 106* - DAVIS‐FRIDAY, PAQUITA Y.; LIU, CHAO‐SHIN; MITTELSTAEDT, H. FRED (Contemporary Accounting Research, 2004)
Abstract This paper examines a fundamental question of interest to researchers and regulators: Does the market treat disclosed financial statement information as if it is less reliable than information recognized in the body of the financial statements? Specifically, we compare the perceived reliability of liabilities for retiree benefits other than pensions (PRBs) disclosed prior to adoption of Statement of Financial Accounting Standards No. 106 (SFAS No. 106) with the perceived reliability of PRB liabilities subsequently recognized under SFAS No. 106. Overall, the evidence is consistent with the market treating disclosed PRB liabilities as less reliable than recognized PRB liabilities and pension liabilities. However, once PRB liabilities are recognized, they do not appear to be any less reliable than pension liabilities. These findings are inconsistent with the Choi, Collins, and Johnson 1997 conclusion that PRB liabilities are inherently less reliable than pension liabilities. The paper also investigates factors that may have contributed to the lower perceived disclosure reliability. Our results suggest that the market perceived PRB liability disclosures to be less reliable when firms provided range disclosures, had higher probabilities of reducing plan benefits, or had lower ratios of retiree to total PRB obligations. These findings suggest that reliability may have been enhanced if more supporting details had been provided in Staff Accounting Bulletin No. 74 disclosures.